2015
DOI: 10.1158/1078-0432.ccr-14-2290
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1/PGC1α-Dependent Increase in Oxidative Phosphorylation Supports Chemotherapy Resistance of Colon Cancer

Abstract: Purpose: Chemotherapy treatment of metastatic colon cancer ultimately fails due to development of drug resistance. Identification of chemotherapy-induced changes in tumor biology may provide insight into drug resistance mechanisms.Experimental Design: We studied gene expression differences between groups of liver metastases that were exposed to preoperative chemotherapy or not. Multiple patient-derived colonosphere cultures were used to assess how chemotherapy alters energy metabolism by measuring mitochondria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
146
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(156 citation statements)
references
References 47 publications
10
146
0
Order By: Relevance
“…PPARGC1A is a major regulator of several key metabolic pathways and coordinates the regulation of genes promoting the conversion of glucose to fatty acids to support tumor growth (17 ). It also plays a pivotal role in inducing the expression of oxidative phosphorylation genes in various tissues, including colon cancer (18,19 ). Increased fatty acid synthesis is important in cancer (20 ).…”
Section: Discussionmentioning
confidence: 99%
“…PPARGC1A is a major regulator of several key metabolic pathways and coordinates the regulation of genes promoting the conversion of glucose to fatty acids to support tumor growth (17 ). It also plays a pivotal role in inducing the expression of oxidative phosphorylation genes in various tissues, including colon cancer (18,19 ). Increased fatty acid synthesis is important in cancer (20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that OXPHOS metabolism is associated with aggressiveness of cancer cells (35) and characterizes cancer cells that have developed resistance to different chemotherapeutic agents in various cancer models (36,37). Conversely, reprogramming toward a hyperglycolytic metabolism has been associated with resistance to biologic agents such as Herceptin and Avastin in breast cancer (12,38).…”
Section: Discussionmentioning
confidence: 99%
“…This aerobic glycolysis phenomenon is often erroneously interpreted as a sign of impaired OXPHOS in cancer. In fact, increasing evidence indicates that cancer cells are reliant on mitochondria for their bioenergetic machinery and macromolecule synthesis function[68], especially when encountering cellular stressors, like chemotherapy[69], radiation therapy[70] or during metastasis[71]. It is therefore not surprising that mitochondrial respiration is being recognized as viable target for cancer therapy[68].…”
Section: Role Of Dead/h Box Proteins In Translating the Cancer Genomementioning
confidence: 99%